Editor’s Foreword - Putkaradze, Tariel (Actual Problems of Kartvelology, 2019)
Actual Problems of Kartvelology is a reviewed annual scientific journal that publishes the materials of international conferences organized by the Kartvelology Centre at the St. Andrew the First Called Georgian University of Patriarchate of Georgia; also reviewed works in linguistics, literary criticism, folklore, historiography, culturology, ethnology and other fields. The current issue of the journal offers the materials of the Scientific Conference Dedicated to the 80th Anniversary of President Zviad Gamsakhurdia (28. 03. 2019). Tariel Putkaradze Editor-in-chief, Professor Head of the Kartvelology Centre St. Andrew the First-Called Georgian University